Community and Cultural Influence on Child Schooling: A Case Study of the Fulani people of Nigeria - Olaniran, Sunday Olawale (Pencerah, 2024)
Recent studies in both developed and developing societies have established a connection between socio-cultural background and child upbringing. While socio-cultural activity is an important factor in a child’s upbringing, there is a dearth of research about how socio-cultural factors hinder child development. This study employs the sociocultural theory of learning to review how the socio-cultural practices of the Fulani people impact the schooling of Fulani children in Nigeria. The Fulani people of Nigeria own over 90 percent of about 15.3 million heads of cattle. It is noted that beef production from Fulani’s cattle farm constitutes a significant portion of the animal protein consumed by the people of Nigeria. However, despite Fulani’s prowess in cattle rearing, which contributes significantly to the economy of Nigeria, their children are highly disadvantaged when it comes to access to qualitative education. The researcher searched through the Directory of Open Access Journals (DOAJ) for literature published between 2014 to 2024 using keywords like cultural influence, sociocultural learning theory, and the schooling of Fulani children. While the study employs the content analysis method to review the existing literature, the question that this presentation seeks to answer is: Why are the children of Fulani people disadvantaged educationally? What does this tell us, the community engagement advocates, about community culture/socio-economic activities, and children’s schooling? How can we organize community engagement and development to support socio-cultural re-engineering efforts?